To obtain the optimum parameters for welding of stainless steel using friction welding technique / Mohd Azne Mohd Yunos - Mohd Yunos, Mohd Azne (2010)
The project attempted to investigate the effect of varying the welding parameters that required welding Stainless Steel by friction welding technique. The parameters involved in this study were heating pressure, heating time, forging pressure and forging time. The scope of the project was to obtain the optimum parameters for welding of Stainless Steel (SS 304) specific on 6mm diameter using friction welding technique. The values were obtained by combining the analysis made on the mechanical properties using Tensile Test and by Visual Inspection. Initially, five (5) welding samples at different heating pressure are conducted at constant heating time, forging pressure and forging time, The tensile strength of each sample is recorded and a graph of strength against heating pressure plotted. The optimum value for the heating pressure was obtained by combining with that of Visual finding. Similar experiments were carried out for the heating time, forging pressure and forging time. The optimum parameters were selected should be balance-up with the visual inspection of weld quality and it's not necessarily due to the higher value of tensile stress. Otherwise, it also depends on the shape of the flash either good shape or over forming of flash. From the findings, it can be concluded that the optimum parameters for welding of stainless steel specific on 6mm diameter using friction welding technique are following; Heating Pressure (20 bar), Heating Time (4 second), Forging Pressure (40 bar) and Forging Time (6 second). (lbar=1.0197kgtfcm2)